Occurrence and Risk Assessment of Tetracycline Residues in Layer Eggs in Haryana, India - Khushbu Bishnoi; Pallavi Moudgil; Deepak Soni; Vijay J. Jadhav (Journal of Food Protection)
Antibiotics are extensively used in layer flocks for the prevention of diseases and to enhance their growth and production. However, their nonprudent use is leading to the occurrence of residues in eggs. The present study aimed at the detection of tetracycline group residues in egg samples collected from layer farms located in Haryana, India, and human health risk assessment. A total of 100 pooled egg samples were analyzed using High-Performance Liquid Chromatography with Ultraviolet detector for the detection of tetracycline group residues. Out of 100 pooled samples, 13 (13%) were found to be contaminated with tetracycline residues (12 for chlortetracycline and one for tetracycline). Of these, five (38.5%) samples (one for tetracycline and four for chlortetracycline) exceeded the maximum residue limit (MRL) established by Food Safety and Standards Authority of India. The risk assessment based on the per capita availability of eggs in Haryana revealed that the current levels of residues in eggs pose no significant toxicological effects on the consumer’s health. The residues exceeding MRL indicate nonprudent use of antibiotics in veterinary practices, which could lead to the emergence of antibiotic resistance. There is a need to generate awareness among farmers toward judicious antibiotic usage in layer birds and adherence to withdrawal periods to prevent the escalating problem of antibiotic resistance.